2013
DOI: 10.1080/15332969.2013.739941
|View full text |Cite
|
Sign up to set email alerts
|

Customer Perception of Services Based on the SERVQUAL Dimensions: A Study of Indian Commercial Banks

Abstract: This article studies the difference in service quality between public sector banks and new generation private sector banks based on the SERVQUAL dimensions as perceived by Indian customers. It also compares banks within these sectors on the given parameters. The authors also develop a perceptual map considering the SERVQUAL dimensions as attributes. The results suggest that the new generation private sector banks are perceived to provide better quality services as compared to public sector banks. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Bose & Gupta, 2013;Jantan & Honeycutt, 2013;Yavas, Babakus, & Ashill, 2007); Pinar, Eser, & Strasser, 2009;Chen, 2002). Be that the case, it would appear from this study that (a) service really is the foundation for recognition, but it is a continually evolving standard upward; (b) more recently, additional factors such as sound management, innovation and financial performance have tended to come into play; and (c) it is possibly easier to be recognized as good if the organization is small.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Bose & Gupta, 2013;Jantan & Honeycutt, 2013;Yavas, Babakus, & Ashill, 2007); Pinar, Eser, & Strasser, 2009;Chen, 2002). Be that the case, it would appear from this study that (a) service really is the foundation for recognition, but it is a continually evolving standard upward; (b) more recently, additional factors such as sound management, innovation and financial performance have tended to come into play; and (c) it is possibly easier to be recognized as good if the organization is small.…”
Section: Discussionmentioning
confidence: 79%
“…Each of these articles not only produced insight into banks in the individual countries, but also provided a background for banking in general. Bose and Gupta (2013), for instance, found that the new generation of private sector banks showed significantly higher scores on four of the five dimensions of SERVQUAL compared to commercial banks. Along similar lines, results from Yavas et al (2007) showed that, regardless of gender, customer perceptions of employee performance in service delivery at the aggregate level are significant correlates of customer satisfaction and positive behavioral intentions.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This method was also created as a consequence of using in practice the service quality model (five gaps model) created by the same team of researchers -the Servqual method basically refers to the last gap -the difference between the consumer's expectations and the perception of the product or service [3]. It can be used to measure quality of different public services, connected with education [4] or healthcare [5,6] and others like bank [7] or air transport [8]. Some of them even have an original name, like for example measuring quality performance of restaurants with DINESERV method [9].…”
Section: Servqual Methodsmentioning
confidence: 99%
“…67][68][69][70][72][73][73]. Although there are other methods for analysing quality of service, such as SERVPERF[74][74], QDF[75][75] and E-S-QUAL[76]…”
mentioning
confidence: 99%